2018
DOI: 10.1089/ars.2017.7359
|View full text |Cite
|
Sign up to set email alerts
|

Redox Sensing by Fe2+in Bacterial Fur Family Metalloregulators

Abstract: The features that determine the disparate reactivity of these proteins with oxidants are still poorly understood. A controlled, comparative analysis of the affinities of Fur/PerR proteins for their metal cofactors and their rate of reactivity with HO, combined with structure/function analyses, will be needed to define the molecular mechanisms that have facilitated this divergence of function between these two paralogous regulators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 121 publications
1
62
0
Order By: Relevance
“…The bacterial intracellular "free" iron concentration is primarily regulated by a global transcription factor Ferric uptake regulator (Fur) (1)(2)(3)(4). It has been generally assumed that when the intracellular "free" iron concentration is elevated, Fur binds "free" ferrous iron and the iron-bound Fur represses the genes encoding for iron uptake systems and stimulates the genes encoding for iron storage proteins (5)(6)(7)(8)(9). The crystallographic studies of the Fur proteins from Escherichia coli (10), Mycobacterium tuberculosis (11), Vibrio cholerae (12), Helicobacter pylori (13), Campylobacter jejuni (14), and Francisella tularensis (15) have revealed that Fur protein exists as a homodimer or tetramer (8) with each monomer containing three putative metal binding sites.…”
Section: Introductionmentioning
confidence: 99%
“…The bacterial intracellular "free" iron concentration is primarily regulated by a global transcription factor Ferric uptake regulator (Fur) (1)(2)(3)(4). It has been generally assumed that when the intracellular "free" iron concentration is elevated, Fur binds "free" ferrous iron and the iron-bound Fur represses the genes encoding for iron uptake systems and stimulates the genes encoding for iron storage proteins (5)(6)(7)(8)(9). The crystallographic studies of the Fur proteins from Escherichia coli (10), Mycobacterium tuberculosis (11), Vibrio cholerae (12), Helicobacter pylori (13), Campylobacter jejuni (14), and Francisella tularensis (15) have revealed that Fur protein exists as a homodimer or tetramer (8) with each monomer containing three putative metal binding sites.…”
Section: Introductionmentioning
confidence: 99%
“…Different redox state sensing mechanisms would be of great importance for bacteria for a fast response to changes in redox state of the external environment of the oral cavity or periodontal pockets, as well as inside the host cells. For example, PerR proteins sense hydrogen peroxide by metal-catalyzed His oxidation, which leads to conformational changes and dissociation from DNA and activation of expression of oxidative stress response genes [74,75]. On the other hand, in the classic OxyR paradigm, H 2 O 2 oxidizes Cys residues, influencing the DNA-OxyR interaction, which leads to the activation of genes encoding proteins with antioxidant function.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidation of PerR leads to loss of the iron cofactor and its dissociation from DNA to derepress transcription of genes involved in the antioxidant response. The mechanistic differences between Fur and PerR from heterotrophic bacteria have recently been reviewed (291). PerR may function as both activator and repressor of gene expression.…”
Section: Regulation By Metal-catalyzed Oxidation: Perrmentioning
confidence: 99%
“…Transduction of these redox signals is frequently carried out by transcriptional regulatory proteins through a variety of mechanisms (237,334,364). Owing to the tight relationship between iron metabolism and redox homeostasis, the activity of many major regulators relies on iron, either as an ion cofactor assembled in iron-sulfur clusters or as heme-based sensors (80,121,134,274,288,291).…”
mentioning
confidence: 99%